Poly[(mu(2)-2,2 `-bipyridine-kappa N-2/N `)bis(mu(3)-2,2,2-trifluoroacetato-kappa O-3/O/O `)disilver(I)] - Arman, H.D.; Miller, T.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
In the title salt, [Ag-2(CF3CO2)(2)(C10H8N2)](n), which may also be regarded as a coordination polymer if long Ag center dot center dot center dot O interactions are considered, each of the N atoms of the somewhat twisted 2,2'-bipyridine molecule [N-C-C-N = -27.5 (4)degrees] binds to an Ag atom, and each of the carboxylate ligands is tridentate, linking to three Ag atoms. The bidentate carboxylate O atoms bridge the same two Ag atoms, resulting in the formation of Ag2O2 rings. These rings are bridged by the 2,2'-bipyridine ligands, forming a chain along the b axis. The chains are linked into double chains via the remaining Ag-O bonds and Ag center dot center dot center dot Ag contacts. As a consequence of the Ag center dot center dot center dot Ag contacts, the NO4 donor set about each Ag atom is heavily distorted. Finally, the chains are linked into a threedimensional network by a combination of C-H center dot center dot center dot O and C-H center dot center dot center dot F interactions.